The Distinction of Inhibiting Factors among Patients who Actively and Inactively Participate in Phase II Cardiac Rehabilitation - Megalita Dwika Stevani; Aan Nuraeni; Eka Afrima Sari (Jurnal Keperawatan Padjadjaran, 2018)
Background: Cardiac rehabilitation (CR) is an important post-acute management for Cardiovascular Heart Disease (CHD) patients. CR has benefits, such as preventing recurrence and improving patients physically. However, the CR participation rate is low. This condition can produce negative effects, such as recurrence and depression. There are inhibiting factors contribute to the CR participation. The purpose of this study is to identify the distinction of inhibiting factors in patients who actively and inactively participate in phase II CR in Bandung. The result will be as advices to improve policy and nursing intervention to improve the participation number of phase II CR in Bandung. Method: This study used comparative design with cross-sectional approach on 72 respondents who recruited by using purposive sampling at a hospital in Bandung, Indonesia. Data were collected by using Cardiac Rehabilitation Barrier Scale (validity r = 0.46-0.55 and reliability 0.887). Data were analyzed by using descriptive frequency and comparative analysis by using Mann-Whitney. Result: It was showed that there were two significant differences between both of the group in terms of health services aspect (p-value = 0.002) and time (p-value = 0.001). However there were no significant differences between both of the group in logistics aspect (p-value = 0.134), and functional status aspect (p-value = 0.057). It indicates that there were distinctions in inhibiting factors on health services and time aspects. Conclusion: There were differences in the health services, which was related to the lack of CR information and also time aspects, which was related to the lack of CR facilities in remote areas. Therefore, providing information about CR and community or home-based CR are needed.